Marching into the Leadership Pipeline: Gender, College Type, and ROTC Participation - Robert Letzler; Signe Janoska-Bedi; Andrew Penner (Socius)
The Reserve Officer Training Corps (ROTC) is the largest single source of military officers in the United States and a major pipeline for Americans to enter military leadership. Although ROTC offers fairly standardized scholarships, curricula, and career paths, the gender composition of ROTC cadets varies substantially across the 323 four-year host campuses. Nine of the 10 ROTC campuses that have the highest percentages of women among their graduating ROTC officers are at Historically Black Colleges and Universities. By contrast, the vast majority of officers graduating from ROTC at senior military colleges such as the Citadel are men.